Hybrid composites of mesenchymal stem cell sheets, hydroxyapatite, and platelet-rich fibrin granules for bone regeneration in a rabbit calvarial critical-size defect model - Wang, Xi (Exp Ther Med, 2017)
The reconstruction of large bone defects remains a major clinical challenge, and tissue engineering is a promising technique for resolving this problem. Many attempts have been made to optimize bone tissue engineering protocols. The aim of the present study was to develop a process incorporating mesenchymal stem cell (MSC) sheets with nanoscale hydroxyapatite (nano-HA) and autologous platelet-rich fibrin (PRF) granules for enhanced bone formation within a critical-sized rabbit cranial defect. MSC sheets and PRF were prepared prior to in vivo experiments. The osteogenic differentiation ability of MSCs and the ultrastructure of PRF were also studied. A total of 15 New Zealand white rabbits were used in the current study and critical-size defects (CSDs) were surgically introduced in the cranium (diameter, 15 mm). The surgical defects were treated with MSC/PRF composites, MSC composites or left empty. Animals were euthanized at week 8 post-surgery. Iconography, histological and histomorphometric analysis were performed to assess de novo bone formation. The percentage of new bone in the MSC/PRF group (35.7±5.1%) was significantly higher than that in the MSC (18.3±3.2%; P<0.05) and empty defect groups (4.7±1.5%; P<0.05). The results of the present study suggest that combined application of an MSC sheet with nano-HA and granular PRF enhances bone regeneration in a rabbit calvarial CSD model, and provides a novel insight into bone tissue regeneration for large bone defects.